Training Leadership and Critical Mind Through SWOT Analysis in 8th Grade Students at Ma’arif Middle School, Batu City - Nuraziza, Chandra Putri; Nugroho, Muhammad Ilham; Yulyantika, Nadya Rindy (Inovasi Lokal, 2024)
A truly moral human means a quality human being who is involved in life, whether as a citizen, leader or being led. Because to become a complete human being, you must know yourself. In order to create a national generation that is superior and competitive and has the spirit of a good leader, the Community Health Science Service team has taken steps to carry out community service in the form of outreach regarding "SWOT Analysis" to students at Ma'arif Batu Middle School so that it is hoped that students will be able to know their strengths, weaknesses, opportunities and threats to himself The implementation method for the "Training Leadership and Critical Mind Through SWOT Analysis in 8th Grade Students at Ma’arif Middle School, Batu City " activity consists of three stages, there are pre-activity devotion, implementation of activity devotion, and post-activity devotion The pre-test and post-test questions consist of 5 questions with multiple choice options. The results of completing the pre-test and post-test for class 8D students at Ma'arif Batu Middle School about SWOT analysis. students'' knowledge increased 27.40% regarding SWOT analysis. This activity also provides benefits for them, namely to recognize internal strengths and weaknesses and understand the organization''s or individual''s external opportunities and threats, so that the organization or individual can anticipate changes in the future, according to their abilities and capacities to achieve their goals.